Social Responsibility Expenses: Tax Aspects to Consider - Belaunde Plenge, Walther (2014)
Corporate Social Responsibility (CSR) is a way of doing business that assumes a more active role in relation to everyone involved in such activity and to anyone who could be affected in anyway by it. Thus, the corporation becomes an agent who must adopt principles and policies for all of its activities, not only to prevent negative consequences but also to obtain larger benefits for its workers, shareholders, neighbors, community, among others.This paper analyses if the expenses on CSR are tax deductible for Income Tax purposes, focusing mainly in what is referred to as social and environmental expenses, which are the ones that demand the most resources.